Peste des Petits Ruminants (PPR)-1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Tih Joseph Shefe, an animal health researcher at the Institute of Agricultural Research for Development, based in Cameroon.